Endothelium-dependent and endothelium-independent vasorelaxant effects of tiliacorinine 12′-O-acetate and mechanisms on isolated rat aorta - Luckika Panthiya (2018)
© 2018 The Authors Tiliacorinine 12′-O-acetate is a modified analog of Tiliacorinine, a major compound in Tiliacora triandra. The present study explored the vasorelaxation property of tiliacorinine 12′-O-acetate and its mechanism in isolated rat aorta using the organ bath technique. Tiliacorinine 12′-O-acetate exhibited concentration-dependent (10−15–10−3.5 M) vasorelaxation in endothelium-intact rings (Emax = 93.53 ± 2.79%) and endothelium-denuded rings (Emax = 74.31 ± 5.09%). The effects of tiliacorinine 12′-O-acetate were attenuated by pre-incubation with N(ω)-nitro-L-arginine methyl ester (L-NAME, endothelium nitric oxide synthase inhibitor) (100 μM), 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ, soluble quanylylcyclase inhibitor) (1 μM), and 4-aminopyridine (1 mM, Kv channel blocker). However, this effect was not impacted by indomethacin (10 μM, cyclooxygenase inhibitor), tetraethylammonium (5 mM, Kca channel blocker), barium chloride (1 mM, KIR channel blocker), or glibenclamide (10 μM, KATP channel blocker). Moreover, pretreatment with tiliacorinine 12′-O-acetate reduced the effect of L-NAME (100 μM) on acetylcholine-induced vasorelaxation. Tiliacorinine 12′-O-acetate showed inhibitory effects on CaCl2-induced contracted rings and reduced the contraction induced by phenylephrine (10 μM) and caffeine (20 mM) in a Ca2+-free solution. The results of this study suggest that tiliacorinine 12′-O-acetate induced endothelium-dependent vasorelaxation through the eNOS/NO/sGC pathway, and also induced endothelium independent vasorelaxation involving the modulation of sGC activity, Kv channels, Ca2+ influx through Ca2+ channels and intracellular Ca2+ release. The data concerning the benefits of tiliacorinine 12′-O-acetate might be further investigated for the application of tiliacorinine 12′-O-acetate as an antihypertensive compound.